SUBJECT-VERB AGREEMENT IN EFL STUDENT’S ESSAY: A DETAILED MORPHO-SYNTACTIC EXAMINATION - Sudar, Sudar (English Review: Journal of English Education, 2024)
The purposes of this study are to identify and to describe morphemes in the subject –verb agreement of EFL student’s Essay writing, second is to describe tenses of subject-verb agreement written in the student’s Essay writing. The third is to describe the dominant tenses of subject-verb agreement in the EFL student’s essay writing. The last is to describe the interferences of EFL student’s first language to their essay writing. It was a descriptive qualitative research. The data was taken from third semester of essay writing classes, in the academic year 2023/2024.The data was analyzed using theory of Morpho-syntactic developed by Andrew, Carstairs & Charthy and Miller, Jim (2002).  Findings revealed that three hundred and forty five clauses that subject-verb agreement contained free and bound morpheme. There were two hundred and fifty nine subjects of clauses contained free morphemes. Then, there were eighty six subjects of clauses contained bound morphemes. Furthermore, there were one hundred and sixty one clauses of verb-agreement contained free morphemes. Then, there were one hundred eighty four clauses of verb-agreement contained bound morphemes. Then, there were two hundred and eighty three clauses that the subject-agreement of clauses was written in present tense. Furthermore, there were sixty one clauses of subject-verb-agreement were written in past tense. Then, there was only one clause used future tense. Then, EFL students essay writing was still influenced by their first language culture. It found that there were one hundred and sixty one clauses contained first language cultures. Further, understanding English linguistics (phonology, morphology, syntax, vocabulary, and spelling) is needed to be learned by EFL students deeply. Then, EFL students’ essay writing   was developed significantly.